Implementasi Internet of Things pada Penyajian Kopi Pintar dengan Sistem Penakaran Berbasis Sensor - Aditya Dwi Saputra; Suryo Sudiro; Agung Nugroho; Muh. Nurfauzi Sahono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The increasing development of Internet of Things (IoT) technology has encouraged innovation in the automation of food and beverage services, including coffee preparation systems. Conventional coffee serving methods still face several challenges, such as inconsistent ingredient measurements, inefficient serving times, and difficulties in monitoring the process remotely. This study aims to design and implement an IoT-based smart coffee serving system equipped with a sensor-based measurement mechanism. The proposed system utilizes an ESP32 microcontroller as the primary controller, an ultrasonic sensor to estimate liquid levels, servo motors to regulate coffee and sugar dispensing, and relay modules to control water pumps. The research employed a Research and Development (R&D) approach, including system design, hardware integration, software development, and functional testing. The results indicate that the developed prototype is capable of performing automatic coffee serving processes while providing real-time monitoring through a web interface. The system is expected to improve serving consistency, reduce human error, and enhance operational efficiency in small-scale coffee service environments.